Bridge Over an Aging Population: Examining Longitudinal Relations Among Human Resource Management, Social Support, and Employee Outcomes Among Bridge Workers - Veth, Klaske N.; Van der Heijden, Beatrice I. J. M.; Korzilius, Hubert P. L. M.; De Lange, Annet H.; Emans, Ben J. M. (Frontiers in Psychology, 2018)
This two-wave complete panel study aims to examine human resource management (HRM) bundles of practices in relation to social support [i.e., leader–member exchange (LMX), coworker exchange (CWX)] and employee outcomes (i.e., work engagement, employability, and health), within a context of workers aged 65+. Based upon the social exchange theory and the Job Demands-Resources (JD-R) framework, it was hypothesized that HRM bundles at Time 1 would increase bridge workers' outcomes at Time 2, and that this relationship would be mediated by perceptions of LMX and CWX at Time 2. Using a longitudinal design, hypotheses were tested in a unique sample of Dutch bridge employees (N = 228). Results of several structural equation modeling analyses revealed no significant associations between HRM bundles, and social support, moreover, no significant associations were found in relation to employee outcomes. However, the results of the best-fitting final model revealed the importance of the impact of social support on employee (65+) outcomes over time.